2019
DOI: 10.1016/j.ultrasmedbio.2019.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Prospective Study of Color Doppler Ultrasound for Breast Masses: Utility of Our Color Doppler Method

Abstract: The use of color Doppler ultrasound (CD) for distinguishing between benign and malignant breast lesions remains controversial. This study (JABTS BC-04 study) was aimed at confirming the usefulness of our CD diagnostic criteria. We evaluated ultrasound images of 1408 solid breast masses from 16 institutions in Japan (malignant: 839, benign: 569). Multivariate analysis indicated that vascularity (amount of blood flow), vascular flow pattern ("surrounding marginal flow" or "penetrating flow") and the incident ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 18 publications
2
30
0
Order By: Relevance
“…Due to the atypical manifestations of breast cancer and the fact that breast cancer with a diameter of <2 cm is relatively difficult to identify by palpation, the disease is associated with relatively high mortality (3). Therefore, the early detection and treatment of breast cancer are of great importance to reduce the incidence and associated mortality (4). The imaging performance of breast cancer, particularly for small tumors, is complex and diverse, leading to ambiguous diagnostic imaging results (5).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the atypical manifestations of breast cancer and the fact that breast cancer with a diameter of <2 cm is relatively difficult to identify by palpation, the disease is associated with relatively high mortality (3). Therefore, the early detection and treatment of breast cancer are of great importance to reduce the incidence and associated mortality (4). The imaging performance of breast cancer, particularly for small tumors, is complex and diverse, leading to ambiguous diagnostic imaging results (5).…”
Section: Introductionmentioning
confidence: 99%
“…Though the study aimed to determine the feasibility of diagnosing lesions utilizing these computer-extracted features, they are not intended to replace a radiologist’s readings, so BI-RADS US classification was retained as a feature. Additionally, a recent study by Watanabe et al found that differences in US between benign and malignant breast masses, especially in the vascularity revealed by CD, can depend on the patient’s age, supporting the selection of age as a feature [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Though utilizing CD for differentiating benign and malignant masses is not currently clinical standard practice, there is much evidence of its potential benefit. Previous studies have shown that CD improves the sensitivity and specificity of cancer diagnosis when utilized with GS US and clinical data [ 5 , 15 , 16 , 17 , 18 , 19 ]. This is thought to be because CD provides unique information on the direction and velocity of blood flow while also minimizing color artifacts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations